Dramatis personae osnową moralności w filozofii Tadeusza Stycznia i Józefa Tischnera - BORKOWSKA-NOWAK, Małgorzata (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The current article describes the way of approaching the human person as an actor in a drama, common to both Styczeń and Tischner. According to both philosophers, the human being, the subject of morality, is a dramatis persona: a «mask» and protagonist of the drama taking place on the stage of the world. The human life is, in turn, the role which is to be played in as perfect a way as possible, with the consideration of the significance as well as the uniqueness of the performance in question. The drama of a human person involves various levels and the article discusses the two most important ones, namely the sphere of cognition, in particular of self−knowledge, and that of freedom. According to Styczeń, the most important moment in the moral life of a human person is that of accomplishing self−knowledge, followed with the discovery of oneself as the subject of one’s actions. In Tischner’s philosophy, in turn, the drama results from the experience of suffering, of pain visible on the face of another human being. As far as the sphere of freedom is concerned, the course of the drama is determined by what happened during its first scene, on the cognitive level.